A Comparative Study of Impunity for Criminals in Iranian Law and International Documents; Cases and solutions - Ali Mansour Lakouraj; asghar abbasi (پژوهشنامه حقوق تطبیقی, 2020)
The article seeks to enumerate the cases of impunity of offenders in Iranian law and international documents, and to examine ways to deal with it; Assuming that this phenomenon cannot be considered acceptable, we decided to state the cases of impunity in Iranian law (amnesty, passage of time, death of the convict, abrogation of the law, pardon of the plaintiff, repentance of the offender and application of the rule of law). Examines the legal principles preventing the punishment of criminals, including the principle of internal criminal law, the principle of non-interference, the principle of immunity in dealing with impunity from the Nuremberg Charter to the Rome Statute. Analyze the International and the International Criminal Court. Also, looking at the history of international law, it can be clearly seen that major international criminals have rarely been held accountable for their actions. So that the only way to punish such criminals can be sought in their defeat in international conflicts. Punishment that is rooted in the revenge of the victorious states and nations, the losers of the war, not in the administration of criminal justice. Finally, it can be said that the existence of impunity in domestic law can be opposed to the principle of punishment and consequently the lack of justice. Second, there is a conflict between the provisions of the Rome Statute, and hopefully the administration of criminal justice through the Court has become possible only in relation to underdeveloped countries. Obstacles to the international community in prosecuting and punishing the perpetrators of these crimes, sometimes rooted in principles Traditional international law, such as the internal nature of criminal law, sovereignty, non-interference and immunity of leaders, which we will analyze below. In the meantime, there is no proper mobility on the part of the Security Council.